Brain Protein Synthesis Rates in the UM-HET3 Mouse Following Treatment With Rapamycin or Rapamycin With Metformin. (13th March 2019) - Reid, Justin J; Linden, Melissa A; Peelor, Frederick F; Miller, Richard A; Hamilton, Karyn L; Miller, Benjamin F
Abstract: Treatment with the mechanistic target of rapamycin (mTOR) inhibitor, rapamycin (RAP), alone and in combination with the antidiabetic drug, metformin (RAP+MET), extends lifespan in mice. The mechanisms underlying lifespan extension are unclear. One possibility is improved capacity for proteostatic maintenance. We have previously characterized peripheral protein synthesis rates following treatment with RAP. However, it is unknown if RAP+MET elicits similar changes, or if either treatment affects protein synthesis in the brain. We hypothesized that 8 weeks of treatment with RAP and RAP+MET would alter brain protein synthesis rates to reflect proteostatic processes. Using the stable isotopic tracer, deuterium oxide (D2 O), we demonstrate in UM-HET3 mice that protein synthesis rates measured in whole brain were unaffected by treatment in young male mice, whereas RAP+MET decreased mitochondrial protein synthesis in young females. Conversely, RAP increased mitochondrial protein synthesis rates in older females. Activity through the AMPK/mTOR pathway was affected in a sex-specific manner in young mice, and minimal changes were observed in the older cohort. Thus, we establish D2 O for measurements of biogenesis in the brain. These results provide initial insights into the effects of RAP and RAP+MET on brain protein synthesis. Additionally, these data emphasize that responses to slowed aging treatments vary with sex and age.